The Effect of Religiosity and Perceived Social Support on Psychological Well-Being - Kennedy, Angelia Pratama; Adriani, Yufi (Presscience, 2023)
This study aims to determine the effect of religiosity (intellectual, ideological, public practice, private practice, and religious experience) and perceived social support (family, friends, and significant others) on psychological well-being. Respondents in this study were 195 people aged 18-21 years, who were teenagers who had lost their parents due to Covid-19, either their mother, father or both, and who live in Greater Jakarta. The questionnaire in this study used measuring instruments adapted from the Scale of Psychological Well-Being (SPWB), Centrality of Religiosity Scale (CRS), and Multidimensional Scale of Perceived Social Support (MPSS). This study uses a quantitative approach, where the validity of each item in the instrument is tested using confirmatory factor analysis (LISREL Software) and the influence of each independent variable on the dependent variable is seen through multiple regression tests (SPSS Software). The results of this study indicate that there is a significant influence between religiosity and perceived social support variables on psychological well-being variables. The influence of all independent variables (IV) on the dependent variable (DV) is 53.1% and 46.9% is influenced by other variables outside this study. Variables that significantly influence psychological well-being are intellectual, religious experience, and friends.